2015
DOI: 10.3346/jkms.2015.30.8.1085
|View full text |Cite
|
Sign up to set email alerts
|

Exuberant Vasculoconnective Component in Mediastinal Mixed Germ Cell Tumors

Abstract: We aimed to evaluate the histologic components of primary mediastinal mixed germ cell tumors. A total of 221 patients diagnosed with a mediastinal germ cell tumor (GCT) were retrospectively reviewed. Among them, 14 patients underwent surgical resection after chemotherapy and 8 patients were diagnosed with mixed GCT, who were then selected for further evaluation. Clinical chart review and histologic review of biopsy and surgical specimens of 8 patients were performed. All 8 patients were young males and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Their cases of 55 patients were associated with yolk sac tumour components, and all specimens were analyzed after chemotherapy. A few similar cases have been published previously, associated with PMTERs independent of prior chemotherapy 142–145 . Recently, a case report also showed a VMT combined with a PMSEMs without prior chemotherapy 146 .…”
Section: Pmgcts With Somatic‐type Solid Malignanciesmentioning
confidence: 65%
“…Their cases of 55 patients were associated with yolk sac tumour components, and all specimens were analyzed after chemotherapy. A few similar cases have been published previously, associated with PMTERs independent of prior chemotherapy 142–145 . Recently, a case report also showed a VMT combined with a PMSEMs without prior chemotherapy 146 .…”
Section: Pmgcts With Somatic‐type Solid Malignanciesmentioning
confidence: 65%
“…However, Cha et al could not reproduce the same pathogenesis in mediastinal GCT, since none of their five cases showed any neural components [10]. They therefore postulated that the benign vasculoconnective component is an intrinsic part of mediastinal mixed GCT [10]. Regardless of pathogenesis, differentiation of this florid benign vascular proliferation from an angiosarcoma is vital given the poor prognostic implications of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to ovarian GCTs, it has been suggested that the expression of growth factors such as vascular endothelial growth factor by the neural component of the teratoma induces vascular proliferation [9]. However, Cha et al could not reproduce the same pathogenesis in mediastinal GCT, since none of their five cases showed any neural components [10]. They therefore postulated that the benign vasculoconnective component is an intrinsic part of mediastinal mixed GCT [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations